Reducing waste generated by international students- mobility - building a business *intelligence dashboard for decision support - Gall, Edwin (2023)
International student mobility is on the rise. Even though international exchange programs foster intercultural development, some contend that the environmental impact must be considered more. This work project focuses on one piece of the complex puzzle: overconsumption. In line with SDG 12, we propose an application called Repurpose, aimed at effectively repurposing everyday items new international students buy but would otherwise throw away at the end of their curriculum. The application is tailored to the global Gen Z audience, leveraging AI for convenient experiences and considering the time gap when international students leave and arrive. Due to its scalable SaaS nature and considerate business model, the app has the chance to grow into a critical application for international students worldwide.